The Problem-identification Process Prior to the Initiation of a Networked Improvement Community - Julie Kallio (Designs for Learning)
In this paper, I present a design case of the problem-identification process prior to the initiation of a Networked Improvement Community (NIC). A NIC is a type of research-practice partnership (RPP) that brings together researchers and practitioners to tackle complex problems of practice, and in doing so, proposes a social reorganization of the traditional education change processes. Central to initiating a NIC, and RPPs more broadly, is the identification of a common problem of practice, but this step often takes place before research on a partnership begins. To investigate how a problem of practice is identified, I use the case of PiPNIC, the Personalization in Practice – Networked Improvement Community, in which a team of university-based researchers used participatory design methods to identify a common problem of practice that would ultimately bring together educators from five schools to participate in the NIC. In the case, I show how the research team constructed a rich problem-solution space and identified a different problem of practice than the research team initially conceived. The problem-identification process, I therefore argue, should be included as a critical component of the NIC initiation framework, and I suggest the “problem-solution space” as a conceptual tool for the joint negotiation of problem identification. The case illuminates how NICs operationalize a social reorganization of research and development in education.